Complete mitochondrial genome of Ctenophthalmus quadratus and Stenischia humilis in China provides insights into fleas phylogeny - Chen, Bin; Liu, Ya-fang; Lu, Xin-yan; Jiang, Dan-dan; Wang, Xuan; Zhang, Quan-fu; Yang, Guo-ping; Yang, Xing (Frontiers in Veterinary Science, 2023)
Fleas (Order Siphonaptera) are common blood-feeding ectoparasites, which have important economic significance. Limited mitochondrial genome information has impeded the study of flea biology, population genetics and phylogenetics. The Ctenophthalmus quadratus and Stenischia humilis complete mt genomes are described in this study. The samples were collected from Jianchuan, Yunnan plague foci, China. The mt genomes of C. quadratus and S. humilis were 15,938 bp and 15,617 bp, respectively. The gene arrangement of mt genome was consistent with that of other fleas, which include 22 tRNA genes, 13 protein-coding genes, and two rRNA genes, with a total of 37 genes. The relationship between C. quadratus and S. humilis in fleas was inferred by phylogenetic analysis of mt genome sequence datasets. Phylogenetic analyses showed that the C. quadratus and S. humilis belonged to different species in the same family, and were closely related to Hystrichopsylla weida qinlingensis in the same family; and revealed that the family Hystrichopsyllidae is paraphyletic, supporting the monophyly of the order Siphonaptera. This study decodes the complete mt genomes of the C. quadratus and S. humilis for the first time. The results demonstrate that the C. quadratus and S. humilis are distinct species, and fleas are monophyletic. Analysis of mt genome provides novel molecular data for further studying the phylogeny and evolution of fleas.